International Islamic University Malaysia (IIUM) student’s acceptance on virtual reality (vr) as a tourism marketing tool - Mohd Tukit, Nuraliah Atika; Abd Rahman, Nur Hidayah (Kulliyyah of Languages and Management, International Islamic University Malaysia, 2019)
Youths are very vulnerable to the rapid development of technology specifically on students. The presence of varieties online applications that can be downloaded on their smartphone have exposed them to the latest technology especially in Virtual Reality (VR) technology. Hence, Technology Acceptance Model (TAM) is applied in this study in order to understand the factors that influencing student’s acceptance in Virtual Reality (VR). Technology Acceptance Model (TAM) is an assessment to predict use and acceptance of information systems and technology by individual user. Technology Acceptance Model (TAM) consists of seven elements which are Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Perceived Enjoyment (PENJ), Interest (INT), Personal Innovative (PI) Accessibility (ACC) and Anxiety (ANX). This study aims to determine the most influence variable using Technology Acceptance Model (TAM) on student’s acceptance. This study is a quantitative study with questionnaires and online survey as the instrumentation in collecting the data. There are 100 students of International Islamic University Malaysia (IIUM) as the respondents of this study from three different campuses, which are Gombak, Kuantan and Pagoh campus. The result of this study displays that the most influence variable in Technology Acceptance Model (TAM) is Perceived Enjoyment (PENJ) while the least influence variable is Accessibility (ACC). This study highlights on the enhancement of the potential to revolutionize the promotion and selling of tourism from tourism player specifically marketer on how to market and promote their destination or product by implementing Virtual Reality (VR) technology in their tourism product and service. Therefore, with the implementation of the new technological advancement in tourism and hospitality industry able to boost up the industry not only to the government but also service provider that generate the benefit by applying Virtual Reality (VR) technology in their business as part of the marketing tool.